G591(P) Glycaemic control improves after continuous subcutaneous insulin infusion therapy: results from an irish regional centre for paediatric type 1 diabetes mellitus. (May 2019) - Ahmed, K; O'Gorman, CS; Neylon, OM; Saunders, J; Lawler, M
Abstract : Objectives: The use of continuous subcutaneous insulin infusion therapy (CSII) in the management of paediatric patients with T1DM has increased substantially in the last decades, and has been shown to contribute to improved glycaemic control particularly in younger age groups. The aim of this study was to evaluate glycaemic control in a population of patients two years after commencing CSII, compared to their pre-CSII glycaemic control. Methods: Retrospective study of prospectively collected data, including 45 eligible paediatric patients with T1DM commenced on CSII during the study period. pre and post CSII factors compared included glycosylated haemoglobin (HbA1c), BMI, insulin dose and severe hypoglycaemic episodes. Parameters were compared in the 6 months prior to CSII to two years post CSII, with data collected in 6 months blocks. Complete data were available on 34/45 patients (13 male, 21 female). Results: When gender, age, time since diagnosis and time on pump are added as factors and covariates to the repeated measures model the trend became non-significant and age appears to have a significant influence on the values (p=0.03). Time since diagnosis (p=0.061, almost significant) and gender (p=0.096, almost significant) appear to be having an effect on the values seen. For BMI, after adjustment for multiple comparisons only the difference between the 0–6 m pre distribution and the 13–18 m distribution post was significant (p=0.024). Table 1 . Conclusion: CSII has significant overall improvement in the first 2 years with a trend of quick reduction in first 6 months, then transient increase followed by slow fluctuant reduction over the second year. This is influenced by age, gender and time since diagnosis. No effect on BMI seen in the first year after CSII.